Poor Physical Function Trajectory Predicts Impaired Patient Survival in Older Recipients of Deceased Donor Kidneys: A Prospective Cohort Study. Issue 11 (7th October 2022) - Tsarpali, Vasiliki; Midtvedt, Karsten; Lønning, Kjersti; Bernklev, Tomm; Åsberg, Anders; von der Lippe, Nanna; Reisæter, Anna Varberg; Heldal, Kristian
Abstract : Background: Optimized health-related quality of life (HRQOL) at the time of kidney transplantation (KT) is associated with improved survival. In older KT recipients, we aimed to prospectively evaluate if HRQOL evolution during the first posttransplant year was associated with long-term patient survival. Methods: Recipients older than 65 y at KT who received an organ from a deceased brain-dead donor and survived >12 mo posttransplant were eligible. HRQOL was assessed pre-KT, at 10 wk, 6 mo, and 12 mo post-KT, using the Kidney Disease Quality of Life Short Form version 1.3 survey. A mixed-effect model was used to explore HRQOL evolution during the first posttransplant year in long-term survivors compared with nonsurvivors. Distinct HRQOL clusters were identified using a group-based trajectory modeling and their association with patient survival was investigated with Cox proportional hazard regression models. Results: We included 192 elderly recipients of deceased brain-dead donor kidneys who were transplanted from 2013 to 2020. Eleven died during the first year leaving 181 for evaluation (male, 125; mean age at KT, 72 y [65–84 y]). During a median observation time post-KT of 4.9 y (11.1–8.5 y), 57 recipients died. In survivors, all the generic and kidney-specific HRQOL domains substantially improved during the first year, whereas in nonsurvivors HRQOL deteriorated. Three longitudinal HRQOL trajectories indicating poor, fair, and good HRQOL evolution were identified. Poor physical function trajectory was significantly associated with higher mortality risk independent of covariates, as compared with good physical trajectory (hazard ratio, 2.38; 95% confidence interval, 1.15–5.01). Conclusions: In elderly KT recipients, detection of declining posttransplant physical function may imply impaired survival. Systematic HRQOL monitoring following KT provides added value when evaluating mortality and may guide therapeutic decisions.